Word Formation Process in SMS Language - Zainab Zaheer (Linguistics and Literature Review, 2017)
Short Message Service (SMS) language can be classified in itself as a variety of written language. The classification of SMS as a distinct variety is based on the uniqueness of the way it is written, since this variety is based only on written form and not speech. This article examines the Word Formation Processes that are used in SMS language by the Bachelor of Business Administration (BBA) students of University of Management and Technology (UMT), Pakistan. The article also explores the choices of Word Formation Processes (WFPs) that are made by males and females. The data was collected from 50 male and 50 female students enrolled in the BBA program of a private university of Lahore. The research questions were related to the use of Word Formation Processes and the research hypotheses were tested to distinguish WFPs as a marker of Gender identity. The results revealed that Standard Word Formation Processes are used more in the SMS language as compared to non-standard WFPs and it also revealed that there is a significant difference in the choices of males and females.